2016
DOI: 10.1007/s12094-016-1532-y
|View full text |Cite
|
Sign up to set email alerts
|

Salvage treatment with irinotecan/cisplatin versus pemetrexed/cisplatin in patients with non-small cell lung cancer pre-treated with a non-platinum-based regimen in the first-line setting: a randomized phase II study of the Hellenic Oncology Research Group (HORG)

Abstract: NCT00614965.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…However, resistance to cisplatin severely affects the effectiveness of chemotherapy. In addition, cisplatin is inevitably associated with common adverse reactions, including alopecia, nausea, vomiting, bone marrow suppression and liver function impairment ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, resistance to cisplatin severely affects the effectiveness of chemotherapy. In addition, cisplatin is inevitably associated with common adverse reactions, including alopecia, nausea, vomiting, bone marrow suppression and liver function impairment ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…The articles analyzed the efficacy of platinum, non-platinum or combination therapeutic regimens while also advocating towards specific treatment modalities. Nine studies advocate for combination therapy as an effective treatment regimen for first-line NSCLC [7][8][9][10][11][12][13][14][15], five studies advocate towards non-platinum based therapy as an effective and safer regimen [8,[16][17][18][19], one study concludes that non-platinum based therapy is an effective regimen compared to combination therapy in first-line NSCLC [20], two studies conclude that both non-platinum based regimens and combination therapy show an equal efficacy [21,22], three therapies indicate similar efficacy between platinum-based and non-platinum based regimens [23][24][25], two therapies indicate that the efficacy of non-platinum based therapy is similar to the efficacy of other treatment regimens [26,27], one study states that platinum-based regimens showed a higher efficacy and response rate than non-platinum based regimens [28], 12 studies advocate for non-platinum based regimens as a second line treatment regimen [29][30][31][32][33][34][35][36][37][38][39][40], and two studies advocate towards combination therapy for second-line treatment [41,42]. Most of the articles lean towards the use of combination therapy for first-line treatment and non-platinum based therapy for second-line treatment.…”
Section: A Brief Analysis Of Resultsmentioning
confidence: 99%
“…It is a highly effective anticancer drug that is frequently utilized in the first-line treatment of solid tumors [ 9 ]. However, Cisplatin treatment is frequently accompanied with various side effects, such as nausea, vomiting, alopecia, liver disorders, and bone marrow inhibition [ 10 ]. Although, the majority of cancer patients respond to platinum, cisplatin-resistance and tumor relapse can be observed among cancer patients [ 9 ].…”
Section: Introductionmentioning
confidence: 99%